2019
DOI: 10.19044/esj.2019.v15n15p279
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de los Sistemas Ganaderos de Aptitud Lechera en el Valle del Quijos, Provincia del Napo, Ecuador

Abstract: ResumenEste trabajo permitió identificar y caracterizar la estructura, función, así como el uso de tecnología de los sistemas ganaderos, sobre las dinámicas espaciales, socioeconómicas y ambientales en las cuales se desarrolla la ganadería en el Valle del Quijos (Ecuador). La metodología se basó en la exploración bibliográfica y el trabajo de campo por medio de observación y encuestas aplicadas en 70 fincas de la región. Como resultado del análisis estadístico, se caracterizó la existencia de cuatro tipologías… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Data from MAGAP 12 have shown that in the Amazon region, cattle raising represents one of the more important activities to generate money resources for these families 2 . In fact, of 5236 agricultural productive units (UPA's) identified in Orellana province, approximately 46% are developed as small livestock farmers with low technological levels and bad management of their biotic resources 2,[13][14][15] . Therefore, in this scenario, no studies have been conducted to explore the udder's health status and can recommend some mastitis control practices.…”
Section: Introductionmentioning
confidence: 99%
“…Data from MAGAP 12 have shown that in the Amazon region, cattle raising represents one of the more important activities to generate money resources for these families 2 . In fact, of 5236 agricultural productive units (UPA's) identified in Orellana province, approximately 46% are developed as small livestock farmers with low technological levels and bad management of their biotic resources 2,[13][14][15] . Therefore, in this scenario, no studies have been conducted to explore the udder's health status and can recommend some mastitis control practices.…”
Section: Introductionmentioning
confidence: 99%